Traffic characterization of VBR MPEG-2 video streams in ATM networks - Wang, Bin (2009)
In this thesis, we propose a simple method which can be used to characterize any pre-compressed variable bit rate MPEG-2 video streams in terms of ATM traffic parameters: Peak Cell Rate, Sustainable Cell Rate, and Maximum Burst Size. Though it is simple to find the PCR parameter, there is generally a very large set of SCR/ MBS pairs that can be used to describe a given video stream. A SCR/ MBS pair is considered most suitable which results in efficient utilization of the network resources provided the Quality of Service commitments can be met. We suggest that the resources should be allocated based on the actual traffic rather than the worst case traffic corresponding to the selected SCR/ MBS pair. The proposed scheme will benefit both, the network operator and the user, since it results in more efficient utilization of the network resources.